Management of Eclampsia Patients Post-ROSC (Return of Spontaneous Circulation) at RSUP M Djamil Padang - Permatasari, Ressy; Emilzon Taslim; Yusrawati (Fakultas Kedokteran Universitas Andalas, 2024)
Background: Eclampsia is a convulsive condition associated with hypertensive disorders in pregnancy which threatens maternal and fetal life which generally requires intensive care. Worsening conditions can complicate multi-organ disorders, coagulation disorders, and infections. Case: A 20 year old, nulliparous woman, preterm gestational age 35-36 weeks of gestation, referred to M Djamil General Hospital with complaints of 3 seizures at home and loss of consciousness. At the time of examination, we found apathetic consciousness; blood pressure of 210/118 mmHg. Urine protein is +3. The patient was terminated by emergency cesarean section. The patient was anesthetized under general anesthesia, and was treated in the postoperative intensive care unit with a ventilator attached. During hospitalization, the patient developed recurrent seizure, laryngeal edema and cardiac arrest, but returned to circulation spontaneously after resuscitation. Hemodynamic and metabolic monitoring is strict on the patient and managed appropriately with good result. Discussion: Eclampsia preceded by preeclampsia is known as a theoretical disease with a two-stage pathogenesis. The principles of eclampsia management are control of seizure, regulation of blood pressure, and termination of pregnancy. Collaboration between multidisciplinary teams determines the success of managing eclampsia cases and improving outcomes for the better.